Communication Skills Training in Pediatric Oncology: Moving Beyond Role Modeling. Issue 6 (29th January 2016) - Feraco, Angela M.; Brand, Sarah R.; Mack, Jennifer W.; Kesselheim, Jennifer C.; Block, Susan D.; Wolfe, Joanne
Abstract : Communication is central to pediatric oncology care. Pediatric oncologists disclose life‐threatening diagnoses, explain complicated treatment options, and endeavor to give honest prognoses, to maintain hope, to describe treatment complications, and to support families in difficult circumstances ranging from loss of function and fertility to treatment‐related or disease‐related death. However, parents, patients, and providers report substantial communication deficits. Poor communication outcomes may stem, in part, from insufficient communication skills training, overreliance on role modeling, and failure to utilize best practices. This review summarizes evidence for existing methods to enhance communication skills and calls for revitalizing communication skills training within pediatric oncology.